Etos Membaca Mahasiswa Jurusan Gizi FKM UIN Sumatera Utara - Harmita Siringo-ringo; Irwansyah Alfaqih; Miranda Situmeang (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The purpose of this research is to find out the reading ethos of students in the Department of Nutrition FKM UIN North Sumatra. Using a questionnaire to gather information from a sample of students in the Gorontalo State University information engineering department, the research used descriptive statistics for data analysis. Reading is a valuable skill that offers many benefits, including broadening one's understanding of the world, improving critical thinking and problem-solving abilities, and encouraging personal growth and development. There are several reasons why reading is important, and this study aims to explore these reasons. The research's conclusions are as follows: 1) Students majoring in nutrition still have a relatively low interest in reading books; this is probably because they become bored easily. 2) Students understand the value of reading books despite the findings showing a low interest in reading. 3) Students believe that reading may enhance their capacity for critical thought, that reading can alter their perspective on a subject, that reading can facilitate their academic progress, and that reading can have long-term advantages.